Students’ Voice Towards the Translanguaging Practices in EFL Classroom - Sakkir, Geminastiti; Amir, Fitrah Al; Atmowardoyo, Haryanto; Limbong, Sunarlia (Journal of English Education and Teaching, 2024)
This study aimed to find out how students’ perceptions of translanguaging practices in EFL classroom. This study used a qualitative research approach. The data for this study was gathered through interviews using a qualitative descriptive method. The interview process was conducted with five students from class IX.2 SMPN 4 Bulukumba. The findings showed that students believed translanguaging makes them learn English more easily, feel comfortable in class, communicate with the teacher effectively, be more interested in learning, and add new vocabulary. Some students explained that they experienced difficulty during the use of translanguaging by the teacher, but most of them realized the importance of translanguaging in developing their English skills. Based on the results of the research, it can be concluded that the implementation of translanguaging has a positive impact in the process of teaching and learning English in EFL classroom. So, for English teachers, it is recommended to use translanguaging in classes where students’ English ability is still low with the aim that students can understand the material better, create a supportive environment, and encourage students to be active in class. Therefore, the use of translanguaging should be balanced and not replace the use of English as a whole.